The inhibitory effects of sorbate and benzoate against Clostridium perfringens type A isolates. (June 2015) - Alnoman, Maryam; Udompijitkul, Pathima; Paredes-Sabja, Daniel; Sarker, Mahfuzur R.
Abstract: This study evaluated the inhibitory effects of sorbate and benzoate against Clostridium perfringens type A food poisoning (FP) and non-food-borne (NFB) disease isolates. No significant inhibition of germination of spores of both FP and NFB isolates was observed in rich medium (pH 7.0) supplemented with permissive level of sodium sorbate (0.3% ≈ 0.13 mM undissociated sorbic acid) or sodium benzoate (0.1% ≈ 0.01 mM undissociated benzoic acid) used in foods. However, these levels of sorbate and benzoate effectively arrested outgrowth of germinated C. perfringens spores in rich medium. Lowering the pH of the medium increases the inhibitory effects of sorbate and benzoate against germination of spores of NFB isolates, and outgrowth of spores of both FP and NFB isolates. Furthermore, sorbate and benzoate inhibited vegetative growth of C. perfringens isolates. However, the permissible levels of these organic salts could not control the growth of C. perfringens spores in chicken meat stored under extremely abusive conditions. In summary, although sorbate and benzoate showed inhibitory activities against C. perfringens in the rich medium, no such effect was observed in cooked chicken meat. Therefore, caution should be taken when applying these organic salts into meat products to reduce or eliminate C. perfringens spores. Highlights: High levels of sorbate and benzoate inhibit Clostridium perfringens spore germination. Sorbate and benzoate block outgrowth of spores of tested C. perfringens strains. Sorbate and benzoate exhibit highest inhibition of spore outgrowth at pH 6.0. Permissive levels of sorbate and benzoate arrest growth of C. perfringens cells. Permissive level of sorbate or benzoate is unable to control C. perfringens in meat.